Sensitivity of Goce Gradients on Greenland Mass Variation And Changes in Ice Topography - Herceg M.; Tscherning C. C.; Levinsen J. F. (Journal of Geodetic Science)
The Gravity field and steady state Ocean Circulation Explorer (GOCE) maps variations in the gravity field by observing second order derivatives (gradients) of the Earth gravitational potential. Flying in the low altitude of 255 km and having a spatially dense data distribution of short wavelengths of the gravity field, GOCE may be used to enhance the time varying gravity signal coming fromthe GRACE satellites.